Determination of the biological efficiency of microbial transformation of organic substances of champignon substrates using biodestructors and their importance as organic fertilizer of plants - Ivanova, T.; Podmarkova, K.; Patyka, M.; Gruzinsky, S.; Chabanyuk , I. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2020)
Goal. Determination of the biological effect of microbial transformation of organic substances of mushroom substrates for the use of biodestructors.Methods. The subject of the study was the used waste substrate after growing mushrooms. The biodestructors Extrakon and Bionorma Destructor were used for the transformation of organic substances of champignon substrates. Winter wheat ‘Smuglyanka’ variety was used as a test object. Research methods: biotechnological, biochemical, microbiological, statistical, light microscopy.Results. Scientific research was carried out and the literature data on the study of waste mushroom substrates and their use as an organic fertilizer were summarized. The monitoring of the possibilities was carried out using substrates after mushroom cultivation. The influence of domestic Extrakon and the Bionorma Destructor on spent mushroom substrates was studied. Established the benefits of using microfertilizer Extrakon and Bionorma Destructor on spent champignon substrates when growing agricultural plants using the example of winter wheat. The research results showed that when using an extract from a spent mushroom substrate, the stem length of the model increases 43.15% longer, and the root length is 1.17% longer, compared to distilled water. When we used an extract from a spent mushroom substrate fermented by Extrakon, the stem length of the model object is 25.12% longer, in comparison with the control, it is 79.11% longer. The length of the roots is 35.66% more compared with the use of an extract from an unfermented spent mushroom substrate, compared with the control — 37.24% more. When Destructor Bionorma was used, the growth of the model object is inhibited.Conclusions. Preparation Extrakon with a spent mushroom substrate in plants, the root system increases due to this, and the feeding area increases. This is due to the fact that the preparation Extrakon is designed for introduction into the soil and for its use the beneficial microflora of the soil is activated, transforms the components of the spent liver substrate, which are then absorbed by the plants and positively affect the nutrition of the root system.